Capacity Building for Islamic Boarding School Students through Health Management Training at Alam Indonesia Islamic Boarding School, Barru Regency - Rini Anggraeni; Nurmala Sari; Herlina Hamzah; Yuyun Widaningsih; Nur Latifah Salman; Andi Azisah Bari’ah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Islamic boarding schools (pesantren) often face health problems such as overcrowding, poor sanitation, and low awareness of clean and healthy living behavior (PHBS). This community service program aimed to improve students’ knowledge and skills in managing health at Pondok Pesantren Alam Indonesia, Barru Regency, through a Training of Trainer (ToT) approach. The program, conducted by the Faculty of Public Health, Hasanuddin University, involved 52 students from junior and vocational levels. Activities included lectures, group discussions, practical sessions, and knowledge tests with 40 questions. Results showed that most students achieved good (34.62%) and fair (30.77%) knowledge levels and improved healthy habits such as eating fruits and vegetables, drinking enough water, and exercising regularly. The program effectively increased students’ awareness and skills in health management and strengthened cooperation between the pesantren and the local government.